THE IMPORTANCE OF BREASTFEEDING IN CHILD GROWTH AND DEVELOPMENT IN SCHOOL PHASE - Joane, Ákila; Silva Teixeira dos Santos, Aryanne; Santos da Silva, Camila; Oliveira S. da Rosa, Fernando; Gabriele Rabelo dos Santos, Helen; Marques Rabelo, Laila; Gomes Bastos, Lara; Reis da Cruz, Neila (Health and Society, 2021)
This paper aims to report the importance of breastfeeding in the growth and development of children in the school phase, since it is found that, despite campaigns and divulgations by the responsible organs, the importance of breastfeeding, breastfeeding rates in Brazil are lower than recommended. The methodology used was a quantitative cross-sectional study, in which a survey was conducted through structured questionnaires sent to mothers of 10 students aged 7 to 10 years in the city of Catu/BA. The result of this study, according to BMI verification, by age shows that 8 of the 10 children in question are of ideal weight, 1 is overweight and 1 is obese. As for breastfeeding, 100% of children were breastfed for an average of 1 year and 5 months, and 70% of mothers did not use resources to help and 30% introduced couscous. It is concluded that the support of health professionals and organs is extremely important to emphasize exclusive breastfeeding up to 6 months of life of a child and breastfeeding up to 2 years of age.